Data Analysis and Data Classification in Machine Learning using Linear Regression and Principal Component Analysis - B S, Lokasree (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper step-by-step procedure to implement linear regression and principal component analysis by considering two examples for each model is explained, to predict the continuous values of target variables. Basically linear regression methods are widely used in prediction, forecasting and error reduction. And principle component analysis is applied for facial recognition, computer vision etc. In Principal component analysis, it is explained how to select a point with respect to variance. And also Lagrange multiplier is used to maximize the principle component function, so that optimized solution is obtained